Controlled Doping of Large‐Area Trilayer MoS2 with Molecular Reductants and Oxidants. (7th January 2015) - Tarasov, Alexey; Zhang, Siyuan; Tsai, Meng‐Yen; Campbell, Philip M.; Graham, Samuel; Barlow, Stephen; Marder, Seth R.; Vogel, Eric M.
<x xml:space="preserve">Abstract</x> Highly uniform large‐area MoS2 is chemically doped using molecular reductants and oxidants. Electrical measurements, photoemission, and Raman spectroscopy are used to study the doping effect and to understand the underlying mechanism. Strong work‐function changes of up to ±1 eV can be achieved, with contributions from state filling and surface dipoles. This results in high doping densities of up to ca. 8 × 1012 cm−2. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>